Political ideology and views about climate change in the European Union. Issue 2 (3rd March 2016) - McCright, Aaron M.; Dunlap, Riley E.; Marquart-Pyatt, Sandra T.
ABSTRACT: There is a strong political divide on climate change in the US general public, with Liberals and Democrats expressing greater belief in and concern about climate change than Conservatives and Republicans. Recent studies find a similar though less pronounced divide in other countries. Its leadership in international climate policy making warrants extending this line of research to the European Union (EU). The extent of a left–right ideological divide on climate change views is examined via Eurobarometer survey data on the publics of 25 EU countries before the 2008 global financial crisis, the 2009 'climategate' controversy and COP-15 in Copenhagen, and an increase in organized climate change denial campaigns. Citizens on the left consistently reported stronger belief in climate change and support for action to mitigate it than did citizens on the right in 14 Western European countries. There was no such ideological divide in 11 former Communist countries, likely due to the low political salience of climate change and the differing meaning of left–right identification in these countries.